ACHIEVING INCLUSIVE FINANCE THROUGH TRAINING AND ASSISTANCE ON FINANCIAL MANAGEMENT AND REPORTING: MEWUJUDKAN KEUANGAN INKLUSIF MELALUI PELATIHAN DAN PENDAMPINGAN PENGELOLAAN DAN PELAPORAN KEUANGAN - Firmandani, Wahyu; Eriani, Izmi Dwira; Sophia, Elsha; Nugroho, Kansa Imeliana Putri; Larasati, Galuh Ayu; Sulthani, Alif Iqbal (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: In the face of intense global competition, micro, small, and medium enterprises (MSMEs) must be able to compete and expand their businesses internationally. One crucial step in addressing these challenges is acquiring adequate knowledge to manage finances and maintain accurate financial records. Objective: This community service project aims to enhance the financial management and reporting knowledge and skills of MSMEs in Gresik Regency. Method: The program was conducted through three main stages: planning, implementation, and evaluation. The planning stage involved needs assessment and regular coordination with partners. The implementation stage consisted of lectures, case discussions, Q&A sessions, and hands-on assistance in using the SIAPIK financial reporting application. The evaluation stage involved pre-tests, post-tests, and discussion-based assessments. Results: The MSMEs participants demonstrated improved knowledge in financial management, including planning, recording, reporting, and financial control, as reflected by an increase in average test scores from 63 (pre-test) to 91 (post-test). Furthermore, with guidance on using the SIAPIK application, the participants were able to prepare digital financial statements. Conclusion: Training and assistance in financial management and reporting had a significant impact on promoting inclusive finance among MSMEs.